New records of the genus Hypogastrura (Collembola: Hypogastruridae) from the Greater Caucasus, with the description of a new species from the monticola-group - Antipova, Maria; Babenko, Anatoly (Zootaxa, 2024)
A new species of the genus Hypogastrura is described from the North Caucasus: H. metegensis sp. nov. The species shares the unusual absence of lateral sensillum S9 on Ant. IV with only four congeners of the monticola-group which it belongs to, but it can be distinguished from all by the relatively long mucro with lower lateral lamellae. Regional records of and taxonomic notes with partial DNA sequences of their mitochondrial cytochrome c oxidase subunit 1 (COI) gene on two other Caucasian species of the same genus are also given.